THE APPLICATION OF RESPIRATORY MUSCLE STRETCHING TECHNIQUES IN ASTHMA PATIENTS WITH INEFFECTIVE BREATHING PATTERNS: A CASE STUDY - Sukma, Ferisa Derry Bunga; Prastiwi, Firman (Universitas Kusuma Husada Surakarta, 2026)
Background: Asthma is a chronic inflammatory airway disease that causes the airway to narrow. Asthma patients experience ineffective breathing patterns. To overcome ineffective breathing patterns, the respiratory muscle-stretching technique can be used. The purpose of this study was to determine the increase in oxygen saturation and decrease in respiratory rate after administering the Respiratory Muscle Stretching technique. Methods: The study used a descriptive, case study design. It involved one asthma patient who experienced ineffective breathing patterns.Results: The case study shows that applying a respiratory muscle-stretching intervention for 1x6 hours, with a training duration of 15 minutes, increased oxygen saturation from 93% to 96% and decreased breathing frequency from 28 times/minute to 24 times/minute.Conclusion: Based on the case study results, respiratory muscle stretching techniques are effective in reducing breathing frequency and increasing oxygen saturation in asthma patients with ineffective breathing patterns.